2006
DOI: 10.1051/rnd:2006009
|View full text |Cite
|
Sign up to set email alerts
|

Long term effect of post-weaning rhythm on the body fat and performance of rabbit doe

Abstract: -Reproductive protocols based on standard (Control: 11 days post-partum) or extended rhythm (PW: post-weaning at 27 days post-partum) were compared. Two groups of fifty 19-weekold New Zealand White females were inseminated for seven consecutive cycles. The kits were weaned at 26 days. On the day of AI, all the does were submitted to ultrasound scanning of the perirenal regions to measure fat thickness. The fertility rate and several indexes of efficiency were calculated. Fat thickness, estimated perirenal fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 13 publications
10
32
0
Order By: Relevance
“…Similarly to our results, Feugier and Fortun-Lamothe (2006) reported differences between females inseminated at 11 d and weaned at 35 d with those inseminated at 25 d and weaned at 23 d. Castellini et al (2006) recorded higher body weight in the groups inseminated at 27 d post-partum. The authors considered this result to be the consequence of a possible better body condition of the latter inseminated group's better condition.…”
Section: Effect Of Reproductive Rhythmsupporting
confidence: 88%
See 4 more Smart Citations
“…Similarly to our results, Feugier and Fortun-Lamothe (2006) reported differences between females inseminated at 11 d and weaned at 35 d with those inseminated at 25 d and weaned at 23 d. Castellini et al (2006) recorded higher body weight in the groups inseminated at 27 d post-partum. The authors considered this result to be the consequence of a possible better body condition of the latter inseminated group's better condition.…”
Section: Effect Of Reproductive Rhythmsupporting
confidence: 88%
“…Castellini et al (2006) found similar results, as the proportion of the replacement does was lower in the group inseminated at 27 d than in the other group where insemination took place at 11 d (60 and 80%, respectively). Higher survival (longevity) could be related to the better body condition (Castellini, 2007).…”
Section: Effect Of Reproductive Rhythmsupporting
confidence: 65%
See 3 more Smart Citations